A survey of opinion and practice regarding prenatal diagnosis of vasa previa among obstetricians from Australia and New Zealand. Issue 3 (16th January 2019) - Javid, Nasrin; Hyett, Jonathan A.; Walker, Susan P.; Sullivan, Elizabeth A.; Homer, Caroline S.E.
Abstract: Objectives: To define current obstetric opinion and clinical practice regarding the prenatal diagnosis of vasa previa in Australia and New Zealand. Methods: A population‐based cross‐sectional survey of Fellows of the Royal Australian and New Zealand College of Obstetricians and Gynaecologists was conducted from April to May, 2016. Descriptive analysis was used to define factors influencing opinion and practice regarding definition of vasa previa, attributable risk factors, and the value of screening. Results: Overall, 453 respondents were included in the study. Two‐thirds (304/453; 67.1%) defined vasa previa as exposed fetal vessel(s) running over or within 2 cm of the internal os. A higher proportion of ultrasound specialists (30/65; 46.2%) preferred a broader definition as compared with generalists (115/388; 29.6%; P <0.001). Overall, Fellows were supportive (342/430; 79.5%) of both reporting ultrasound‐based risk factors at the 20‐week anomaly scan and targeted screening (298/430; 69.3%). Only 77/453 (17.0%) respondents recognized all five "known" risk factors for vasa previa. Conclusions: There was a lack of consensus regarding the definition and diagnosis process for vasa previa. There was also a knowledge gap in risk factors for vasa previa that would inform a targeted screening policy. Nevertheless, support for targeted screening was strong from obstetricians who responded. Abstract : Despite a lack of consensus on the definition of vasa previa, most obstetricians in Australia and New Zealand support targeted screening for vasa previa.